X-ray scattering from warm dense iron - White, S; Nersisyan, G; Kettle, B; Dzelzainis, T; McKeever, K; Lewis, C; Otten, A; Siegenthaler, K; Kraus, D; Roth, M; White, T; Gregori, G; et al. (2013)
We have carried out X-ray scattering experiments on iron foil samples that have been compressed and heated using laser-driven shocks created with the VULCAN laser system at the Rutherford-Appleton Laboratory. This is the highest Z element studied in such experiments so far and the first time scattering from warm dense iron has been reported. Because of the importance of iron in telluric planets, the work is relevant to studies of warm dense matter in planetary interiors. We report scattering results as well as shock breakout results that, in conjunction with hydrodynamic simulations, suggest the target has been compressed to a molten state at several 100GPa pressure. Initial comparison with modelling suggests more work is needed to understand the structure factor of warm dense iron. © 2013.